THE INFLUENCE OF EDUCATION LEVEL, INFRASTRUCTURE AND WORK SKILLS ON EMPLOYEE PERFORMANCE AT THE EDUCATION AND CULTURE OFFICE OF KUPANG REGENCY - Etni Susanti Djo Talo; Melkisedek N. B. C Neolaka; Maria M. Lino (RADJA PUBLIKA, 2026)
This study examines the influence of education level, work infrastructure, and job-related skills on employee performance within a local public education institution in Indonesia. In the context of public sector reform, improving employee performance remains a critical challenge, particularly in education governance at the local level. This research adopts a quantitative approach, collecting data through structured questionnaires administered to 61 employees of the Kupang Regency Education and Culture Office. Data were analyzed using multiple linear regression to assess both partial and simultaneous effects of the independent variables on employee performance. The findings indicate that education level has a positive and statistically significant effect on employee performance, suggesting that higher educational attainment contributes to better work outcomes. Adequate infrastructure also plays a significant role in enhancing performance by supporting more efficient and effective work processes. Furthermore, work skills emerge as a crucial determinant of employee productivity and effectiveness. Simultaneous testing confirms that education level, infrastructure, and work skills collectively explain a substantial proportion of variations in employee performance. This study contributes to the literature on public sector human resource management by highlighting the combined importance of human capital and institutional support in shaping employee performance. The findings suggest that local governments should prioritize continuous education, infrastructure development, and skill enhancement programs to improve organizational performance in the public education sector.